Sedimentary context and palaeoecology of Gigantoproductus shell beds in the Mississippian Eyam Limestone Formation, Derbyshire carbonate platform, central England - Nolan, L.S.P.; Angiolini, L.; Jadoul, F.; Della Porta, G.; Davies, S.J.; Banks, V.J.; Stephenson, M.H.; Leng, Melanie J. (Geological Society, 2017)
A sedimentological study was conducted at two localities exposing the Mississippian Eyam Limestone Formation of the Derbyshire carbonate platform, UK. Ricklow Quarry comprises seven facies with diverse skeletal assemblages, representing deposition on the inner to middle ramp within open marine waters. Once-a-Week Quarry comprises four facies, dominated by crinoidal debris representing deposition on the inner ramp. Both localities expose Gigantoproductus shell beds. Palaeoecological analysis of a single shell bed from each locality enabled investigation of the rapid colonization and success of this taxon on the platform. At Ricklow Quarry, on the eastern side of a localized mud mound, both life (>72% of thin and thick-shelled brachiopods in life position) and neighbourhood assemblages are present. A low-moderate diversity community (<1.37 and <0.8 Shannon diversity index) rapidly established over relict Brigantian mud mounds. Shell beds are preluded by intervals of decreased energy that allowed larvae to settle. Once established, the dominance of thick-shelled individuals enabled baffling, potentially providing localized shelter for larvae and nearby individuals. At Once-a-Week Quarry, where no mud mound is present, only thick-shelled Gigantoproductus species and a low diversity community (<1.07 Shannon diversity index) exclusively comprising neighbourhood assemblages (37% in life position) is present. The presence of inactive mud mounds at Ricklow Quarry appears to have been the key to the success of Gigantoproductus species enabling the onset of stable communities in the shelter provided by the relict mound. Once the first palaeocommunities were established, larvae dispersed and colonized higher energy settings, such as at Once-a-Week Quarry.